1987
DOI: 10.1002/j.1556-6676.1987.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselors and Self‐Help Groups

Abstract: Self‐help groups have become legion in both number and purposes. The authors review the growth of this movement and its current status and suggest ways in which counselors can draw upon such groups in their professional practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, the group also served to create a culture or social system for its members. Human behavior involves interacting in social systems that meet the basic needs for contact, recognition, acceptance, approval, and esteem (Buie, 1987;Goldschmidt, 1963;Riordan & Beggs, 1987;Riordan & Walsh, 1994). Instillation of hope and universality was identified a feature of regular meeting involvement.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the group also served to create a culture or social system for its members. Human behavior involves interacting in social systems that meet the basic needs for contact, recognition, acceptance, approval, and esteem (Buie, 1987;Goldschmidt, 1963;Riordan & Beggs, 1987;Riordan & Walsh, 1994). Instillation of hope and universality was identified a feature of regular meeting involvement.…”
Section: Resultsmentioning
confidence: 98%
“…Self-help treatments have been increasingly recommended to BN clients by health professional as a supplement to their treatment (Carter & Fairburn, 1995;Fairburn & Carter, 1997;Peterson et al, 2001;Riordan & Beggs, 1987;Wilson, Vitousek, & Loeb, 2000). Others have found that an unguided selfhelp approach may offer an effective initial treatment or provide secondary prevention for a subgroup of women with bulimia nervosa (Carter & Fairburn, Downloaded by [University of Toronto Libraries] at 02:01 20 December 2014 1998; Carter, Olmstead, Kaplan, McCabe, Mills, & Aime, 2003).…”
Section: Self-help and The Recovery Processmentioning
confidence: 95%
“…Most adolescent grief and loss studies have been gathered via surveys to assess the prevalence of bereavement experience within the adolescent population and tend to be descriptive in nature (cf. Balk, 1983;Dyregrov et al, 1999;McNeil, Silliman, & Swihart, 1991;Melhem et al, 2004;Noppe & Noppe, 1997;O'Brien et al, 1991;Rask, Kaunonen, & Paunonen-Ilmonen, 2002;Ringler & Hayden, 2000;Riordan & Beggs, 1987;ServatySeib & Pistole, 2007).…”
Section: Adolescent Grief and Loss Reactionsmentioning
confidence: 99%
“…Self-help support groups, such as Alcoholics Anonymous, are popular in the United States. There are approximately one-half million such groups with a total membership of more than 15 million persons (Riordan & Beggs, 1987). The moral inventories and spiritual aspects of Alcoholics Anonymous provide a useful program for internalizing values through actual discovery of spiritual principles and are important in recovery (Alterman, 1981).…”
Section: Self-help Methodsmentioning
confidence: 99%